Mariculture Pond Ecology with Emphasis On Environmental Quality and Production of Penaeus Monodon (Fabricius) - Mustafa Kamal, Abu Hena (2005)
In the present study, mariculture pond ecology with special reference to environmental quality and tiger shrimp Penaeus monodon production in old culture ponds (>3 years) and new culture ponds (4 year) were investigated throughout the culture period in Malacca, Malaysia. The study showed that the cation exchange capacity (CEC) varies with soil texture while soil organic matter varied with the culture pond age. The concentrations of major cations depends on cation exchange capacity of soils attributed partly to chemical bonding or adsorption of colloids. Deposition of nutrient loaded suspended solids through uneaten feeds and other culture activities led to increase in the concentrations of macro and microelements onto the pond bottom at the end of the culture period. The dynamics of macro and microelements in pond and sediment waters were not distinct in old and new culture ponds throughout the culture period, but were influenced by accumulation process of living organisms, water exchange and precipitation of major cation as organic and inorganic particles. Major groups of the macro and meiobenthos comprised of gastropods, polychaetes, bivalves, crustaceans, ostracods, nematodes, insects and crab larvae. Gastropods were the dominant group of macrobenthos followed by harpacticoid copepod as meiobenthos throughout the culture period. The growth of shrimp was related with the macrobenthos (r=0.62, p<0.05) and meiobenthos abundance (r=0.67, p<0.05) in the culture ponds. The major groups of zooplankton in the ponds were copepods, rotifers, sergestidae, luciferans, gastropod larvae, bivalve larvae, pelagic polychaetes, nematodes, crustacean nauplii, insects and mysids. About 18-30% of the total zooplankton population decreased within one month after the release of post larvae into the ponds which revealed the significance of natural foods in culture ponds in reducing the production cost and increasing pond yield. Stomach content analysis showed that the stomach of shrimps contained a wide variety of items depending on the availability of benthic and pelagic organisms in the ponds. Higher content of natural food items were found in the stomach of shrimps collected from the old culture ponds than the new culture ponds. Although a commercial feed was provided, the juvenile, sub adult and adult P. monodon were found to be opportunistic omnivorous scavengers feeding on variety of benthic materials and organisms such as detritus, crustacean, molluscs, polychaetes, rotifers and phytoplankton. In the group of Crustacea, copepods were the major food item preyed by all stages of the shrimps throughout the culture period in the ponds. The diversity of fungi increased at the end of culture period in both old and new culture ponds. The proliferation of fungi in general could be due to shrimp faeces and high carbon source from uneaten feeds as the culture progressed. The present study revealed that population of fungi in shrimp pond sediments were mostly of the genera of Aspergillus and Penicillium which were similar to the terrestrial soil fungi. The results showed that many activities such as feeding, nutrient status, stocking density, weather conditions, accumulation of organic matters, biological factors and pond age governed the quality of pond water, shrimp growth, production and pond ecosystem during the culture period.